The Role of Fraud Diamond in Detecting Fraudulent Financial Statements - Purnamasari, Pupung; Nurcholisah, Kania; Nurleli, N; Lasmanah, L (KnE Social Sciences, 2024)
The implementation of financial statement components in Indonesia has become increasingly comprehensive. However, there are still ample opportunities for management and other parties to commit fraud in financial statements, particularly in the banking sector. The research aims to analyze whether fraud diamond influences the occurrence of fraud in the banking industry. The sample used in this study consists of banking reports from 2018 to 2021, with a total of 120 banks included. The research findings indicate that the pressure variable and rationalization variable have a positive impact on financial statement fraud. On the other hand, the opportunity variable and capability variable do not influence financial statement fraud. The positive results suggest that when management is unable to meet predetermined targets, their motivation to engage in fraudulent activities increases. Additionally, reporting accrual income in the income statement, regardless of whether the cash has been received from customers during that period or not, serves as a motivation for management to present their financial statements more appealingly to investors. Keywords: fraud diamond, fraudulent financial statements, banking sector